Influence of listening in learning mathematics and english language among senior secondary students in Akinyele Local Government, Oyo State (2014)
Students 'performance in mathematics over time has raised and still raising a lot of questions. At the beginning of every academic year, teachers wonder what could be done to make students learn better in the subject. The story with learning English language is also similar. Despite that English language is the language of instruction in Nigerian schools; students still demonstrate consistent gross deficiency in mastering the language. Several factors could be responsible for this development which poor listening habit of students may probably be part of. Hence, this study was designed to examine the influence of listening in learning Mathematics and English Language among Senior Secondary School students in Akinyele local government of Oyo State. Three Hundred and fifty (350) samples were drawn for the survey from selected schools using purposive sampling technique. However, three hundred and ten (310) duly completed copies of the questionnaire were retrieved and used to analyse the data gathered for the study. Also, interviews were conducted with selected teachers in the sample schools. Findings show that teachers employed poor teaching methods which do not give students opportunity to express and interact with one another in the class. Findings also showed that majority of the students have poor listening habits like distracting the teachers while in class, distracting sitting mannerism, engaging inside talks, not answering or asking questions either because they are emotionally unstable in class or because they are scared of their teacher, and also being easily distracted due to environmental factors. The implication of these findings is that students generally do not listen in class; they just hear, and this affects their academic performance in English Language and Mathematics. The result shows that both teachers and students determine the factors that affect students' listening in relation to their academic learning. It is recommended that teachers should try and have good interpersonal relationships with their students and students also should pay more attention in class to enhance their learning in English Language and Mathematics.